Better buildings : learning from buildings in use - Partington, Richard (Architect); Bradbury, Simon (Architect) (RIBA Publishing, 2017)
This book started life as a successor to Sustainable Architecture, published in 2007, which set out to prove that sustainable architecture can indeed both lift the spirit' as well as save the planet. This fully revised edition seeks to take a step further, exploring how sustainable buildings are occupied and work, and sheds light on the methods used to observe this. Through short essays from thought-leaders and case studies of visually stunning, environmentally ground-breaking projects, Better Buildings provides architects with the inspiration and tools they need to deliver sustainable design.